2009
DOI: 10.1007/s12243-009-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

On the cooperative MIMO communication for energy-efficient cluster-to-cluster transmission at wireless sensor network

Abstract: Energy-efficient data transmission is one of the key factors for energy-efficient wireless sensor networks (WSN). Cooperative multiple input multiple output (MIMO) explores the wireless communication schemes between multiple sensors emphasizing the MIMO structure. In this paper, an energy-efficient cooperative technique is proposed for a WSN where selected numbers of sensors at the transmitting end are used to form a MIMO structure wirelessly connected with a selected number of sensors at the receiving end. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The total energy in the case of node selection is EDA+MIMO=EDA+MISO=i=1MtLiFEch+Lchi=1Mt1LiFEinormalt+LchLiFEnormalsnormalt+i=1Mt1LiEinormalt+Edai=1MtLi+(Mnormalt1)Eit0i=1MtLiyi+LnormalcPnormalsLiFi=1xEit0+Enormalbnormalri=1MrLiyi where E ch is the channel estimation energy L ch is the number of bits needed to transmit the channel estimation result. Data size L i is divided by the frame size F to find out the number of channel estimations required for the transmitted data size.…”
Section: Energy Modelmentioning
confidence: 99%
“…The total energy in the case of node selection is EDA+MIMO=EDA+MISO=i=1MtLiFEch+Lchi=1Mt1LiFEinormalt+LchLiFEnormalsnormalt+i=1Mt1LiEinormalt+Edai=1MtLi+(Mnormalt1)Eit0i=1MtLiyi+LnormalcPnormalsLiFi=1xEit0+Enormalbnormalri=1MrLiyi where E ch is the channel estimation energy L ch is the number of bits needed to transmit the channel estimation result. Data size L i is divided by the frame size F to find out the number of channel estimations required for the transmitted data size.…”
Section: Energy Modelmentioning
confidence: 99%
“…Data aggregation reduces the data size but increase the steps in cooperative MIMO communication. The issue is explained in many research papers [1][2][3][4][5][6]. …”
Section: Sensor Networkmentioning
confidence: 99%
“…Moreover, physical implementation of multiple antennas at a small node may not be feasible. As solutions to the latter problem cooperative MIMO (C-MIMO) and virtual antenna array concepts have been proposed to achieve MIMO capability in a network of single antenna [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to reduce the energy consumption of sensors since energy efficiency optimization is a very important critical issue in system design of WSN. The results have shown that in some cases, MIMO-based cooperative systems for WSN lead to better energy optimization and smaller end-to-end delay compared to the traditional singleinput single-output (SISO) approach even after taking into account the additional circuit power, communications, and training overheads [10]. These cooperative systems were based on space-time block codes (STBC).…”
Section: Introductionmentioning
confidence: 99%